PERTIMBANGAN HAKIM DALAM PEMIDANAAN PELAKU PEMBUAT IKLAN PERUSAHAANDI INTERNET TANPA IZIN - Etieli Buulolo (Jurnal Panah Hukum, 2024)
The crime of creating illegal business advertisements on the Internet is the crime of taking advantage of another person's business position to deceive people via the Internet. Decision No. 819/Pid.Sus/2016/PN. Jmb is one of the decisions regarding the conduct of corporate advertising without permission on the Internet. This study uses a type of normative legal research with a legal approach, a case approach, a comparative approach and an analytical approach. Based on the research results and discussion, we can conclude. Based on research findings and discussion, it can be concluded that the judge's considerations in decision number 819/Pid.Sus/2016/PN. Jmb in the conviction of perpetrators who create company advertisements on the internet without permission must be proven in accordance with Article 184 of the Criminal Procedure Code and also based on proven facts in the trial and has fulfilled the elements of Article 35 of Law Number 11 of 2008 concerning Electronic Transaction Information, so that the panel of judges believes that the defendant has been legally and convincingly proven guilty of committing the criminal act for which he was charged, namely "intentionally and without right or against the law carrying out manipulation, creation, alteration, disappearance, destruction of Electronic Information and/or Electronic Documents with the aim of making the Electronic Information and/or Documents "The electronic data is considered as if it were authentic data," so that the judge sentenced the defendant to prison for 2 (years). Whereas in this decision, the judge did not impose a fine on the defendant, which in essence the defendant's actions were very detrimental to the victim, so what if On the other hand, it was seen that the judge's decision was unfair. The author suggests that in handling criminal cases of manipulation, creation and alteration of electronic information, judges must consistently consider the juridical, philosophical and sociological aspects. This is important so that the criminal sanctions imposed are in accordance with the error committed by the defendant, without discriminating against the individual's background.